Answer:
x = -1 y = -1
Step-by-step explanation:
x + 3y = −4
x + 5y = −6
Multiply the first equation by -1
-x - 3y = 4
The add to the second equation to eliminate x
-x - 3y = 4
x + 5y = −6
--------------------
2y = -2
Divide by 2
2y/2 = -2/2
y = -1
Now solve for x
x+3y = -4
x +3(-1) = -4
x -3 = -4
Add 3 to each side
x-3+3 = -4+3
x = -1
Answer:
A.1 square and 4 triangles
Step-by-step explanation:
A pyramid has sides that are triangular faces and a base. In a square pyramid, the base is a square.
The net therefore has 1 Square and 4 Triangles.
A net is given in the attached diagram:
Answer:
(t•s )(x) = 4x^3 - 29x^2 + 10x - 21
Step-by-step explanation:
(t•s )(x) is the product of functions s and t:
(t•s )(x) = ( 4x^2 - x + 3)(x - 7). Applying the Distributive Property of Multiplication, we get:
(t•s )(x) = 4x^3 - 28x^2 - x^2 + 7x + 3x - 21
which needs to be simplified by combining like terms:
(t•s )(x) = 4x^3 - 29x^2 + 10x - 21